STUDI PERACANCANGAN SISTEM JANGKAR DAN TAMBAT PADA KAPAL KARGO 14.715 DWT BERDASARKAN BKI CLASS - Triyanti Irmiyana; Akhmad Maulidi; Heni Siswanti; Windra Iswidodo (Techno Bahari, 2020)
Cargo Ship Planning is very important for sea transport. One of the important factors in ship planning is the determination of the anchor and mooring system which functions as a tool to limit the motion of the ship when it is anchored outside the port, so that the ship remains in its position even though it is under pressure from sea currents, wind and waves.. The formulation of the problem in this study is the number of anchors and the motor power of the anchor system on a cargo ship based on the BKI class. The purpose of this study is to determine the number of anchors and the motor power of the anchor system on a cargo ship based on the BKI class. The research method of anchor system analysis was carried out by using a literature study method based on BKI class 2014 volume II. The conclusion of this research is knowing the number of anchors as much as 2 pieces, the length of the anchor chain with the anchor chain length of 522.5 m, the diameter of the anchor chain is 60 mm, and the motor power of the windlass is 1.7 HP. While the length of the mooring rope along the 280 m is 4 pieces